Variation order for additional item for internal electrification & IT work - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for variation order for additional item for internal electrification & IT work of Brac University new campus project.